PERBANDINGAN KINERJA KEUANGAN PT CISADANE SAWIT RAYA TBK DAN PT PP LONSUM SUMATRA INDONESIA TBK : ANALISIS RASIO DAN TREN PERIODE 2019 - 2023 - Yolanda, Feby; Al Ihsan, Muhammad Ali; Rafika, Mulya (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze and compare the financial performance of PT Cisadane Sawit Raya Tbk (CSRA) and PT PP London Sumatra Indonesia Tbk (LSIP) for the 2019–2023 period using financial ratio analysis and trend analysis. The methods used include liquidity, profitability, solvency, and activity ratios to assess the efficiency and financial stability of the two companies. The results show that LSIP has a more stable and high level of liquidity than CSRA, reflecting better cash management. In terms of profitability, CSRA experienced a more significant increase in Gross Profit Margin (GPM), but still needed to increase Net Profit Margin (NPM). In contrast, LSIP faces challenges in cost efficiency with a more stable NPM. In terms of solvency, CSRAs have decreased debt dependency but are still above industry standards, while LSIP has a healthier capital structure and lower financial risk. In terms of activities, CSRA shows an increase in the efficiency of asset use even though it is still below industry standards, while LSIP also needs to improve the effectiveness of its asset management. Overall, this research provides insight for investors and company management in designing more optimal financial strategies.